2019
DOI: 10.1371/journal.pone.0217144
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of spatiotemporal patterns of historic natural Anthrax outbreaks in Minnesota and Kazakhstan

Abstract: Disease spread in populations is a consequence of the interaction between host, pathogen, and environment, i.e. the epidemiological triad. Yet the influences of each triad component may vary dramatically for different settings. Comparison of environmental, demographic, socio-economic, and historical backgrounds may support tailoring site-specific control measures. Because of the long-term survival of Bacillus anthracis , Anthrax is a suitable example for studying the influence of triad c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…The cumulative number of leptospirosis cases for the entire observation period per unit area by the districts (G-rate) was chosen as a measure for the intensity of the leptospirosis epidemic within the study area (46)(47)(48)(49). The Forest-based Classification and Regression method was applied to identify the relationships between the log-transformed G-rate and a set of potential explanatory factors (50, 51).…”
Section: Assessment Of the Relationship Between Leptospirosis Incidence And Geospatial Factorsmentioning
confidence: 99%
“…The cumulative number of leptospirosis cases for the entire observation period per unit area by the districts (G-rate) was chosen as a measure for the intensity of the leptospirosis epidemic within the study area (46)(47)(48)(49). The Forest-based Classification and Regression method was applied to identify the relationships between the log-transformed G-rate and a set of potential explanatory factors (50, 51).…”
Section: Assessment Of the Relationship Between Leptospirosis Incidence And Geospatial Factorsmentioning
confidence: 99%
“…Anthrax, caused by a spore-forming bacterium Bacillus anthracis, is characterized by the prolonged survival of the spores on soil and wide range of hosts including wildlife, livestock, and human (201,202). Therefore, the observational study designs on Anthrax are likely to be retrospective based on reported cases (203). Given Anthrax is reportable to the animal and public health authorities, most likely type of data available would be point-referenced in nature (i.e., presence of the disease at farm locations or grazing lands).…”
Section: How To Use the Framework To Choose Sat: An Examplementioning
confidence: 99%
“…Given the prolonged survival of Anthrax spores in contaminated soils/environment, in addition to the initial testing for spatial dependence, understanding the spatiotemporal dependence and spatiotemporal directionality is the key to understand the extent of past spread of the disease. Testing whether there are space and time clustering in the data would facilitate determining any particular area/s with high relative risk for disease clusters at a specific time [i.e., disease hot-spots; (203)].…”
Section: How To Use the Framework To Choose Sat: An Examplementioning
confidence: 99%
See 2 more Smart Citations